Phytochemical screening and anti-obesity activity of zingiberaceae rhizome ethanolic extract - Daud, Dzulsuhaimi; Suary, Nick; Jamahir, Aleya Maisara; Nazri, Aleeya Shamimi; Mohamad-Helmi, Puteri Iylia Maisarah; Anuar, Nurizzati Syafieya; Mohd, Nur Fazween Batrisyia; Tawang, Alene; Mat-Said, Zahid (2025)
The prevalence of obesity as a global health concern has prompted increasing interest in plant-based therapeutics with bioactive potential. This study aimed to comparatively evaluate the phytochemical profiles and anti-obesity activities of Zingiber officinale, Curcuma longa and Alpinia galanga rhizomes ethanolic extracts. Qualitative screening technique was used to determine their phytochemical constituents and pancreatic lipase inhibition assay was used to determine their anti-obesity capacities. All three extracts revealed abundant phytoconstituents, with variation in intensity, suggesting diverse bioactive potentials. Anti-obesity results indicated that Z. officinale ethanolic extract exhibited moderate pancreatic lipase inhibitory effect, while C. longa and A. galanga showed low but consistent activity across the assays (dose dependent response). These findings suggest that rhizomes from the Zingiberaceae family possess anti-obesity potential at differencing levels. Further investigations on isolation of active compounds and animal trials are recommended.